1998
DOI: 10.1007/s005950050213
|View full text |Cite
|
Sign up to set email alerts
|

Micrometastatic Colorectal Cancer Lesions in the Liver

Abstract: A surgical resection of metastatic liver lesions from colorectal cancer contributes to an improved prognosis. However, the postoperative recurrence rate remains high, particularly in the residual liver. This is probably the result of the failure to detect small lesions. In the present study, we histologically examined the presence of intrahepatic micrometastases, which are considered to be related to recurrence in the residual liver. Intrahepatic micrometastases were histologically examined in 31 resected spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Local tumour recurrence may be due to incomplete destruction of the tumour lesion or to stimulation of satellite micrometastases. Indeed, examination of resection specimens has shown that more than 50 per cent of colorectal liver metastases are surrounded by microsatellite lesions 27 . Improved imaging and RFA procedures are needed to minimize incomplete destruction of the tumour mass 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Local tumour recurrence may be due to incomplete destruction of the tumour lesion or to stimulation of satellite micrometastases. Indeed, examination of resection specimens has shown that more than 50 per cent of colorectal liver metastases are surrounded by microsatellite lesions 27 . Improved imaging and RFA procedures are needed to minimize incomplete destruction of the tumour mass 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Improved imaging and RFA procedures are needed to minimize incomplete destruction of the tumour mass 28 . However, RFA is unlikely to be effective in eradicating satellite micrometastases, at least in part owing to their invisibility using current imaging modalities 27 . Adjuvant chemotherapy or targeted therapy may therefore have a place in the treatment of patients with colorectal cancer undergoing RFA treatment for colorectal liver metastases.…”
Section: Discussionmentioning
confidence: 99%